2021
DOI: 10.3390/jcm10163607
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Achalasia: Updates of the Last Two Years

Abstract: Achalasia is a rare neurodegenerative disorder causing dysphagia and is characterized by abnormal esophageal motor function as well as the loss of lower esophageal sphincter (LES) relaxation. The assessment and management of achalasia has significantly progressed in recent years due to the advances in high-resolution manometry (HRM) technology along with the improvements and innovations of therapeutic endoscopy procedures. The recent evolution of HRM technology with the inclusion of an adjunctive test, fluoros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
(84 reference statements)
0
15
0
2
Order By: Relevance
“…The most common symptoms are dysphagia for both solids and liquids, regurgitation, and chest pain 1 . In addition to Heller myotomy and esophagectomy, 2 POEM has been established as a principal endoscopic therapeutic procedure in recent years 2,3 . Esophageal achalasia induces lung abnormalities due to dilatation of the esophagus and recurrent microaspiration 4 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptoms are dysphagia for both solids and liquids, regurgitation, and chest pain 1 . In addition to Heller myotomy and esophagectomy, 2 POEM has been established as a principal endoscopic therapeutic procedure in recent years 2,3 . Esophageal achalasia induces lung abnormalities due to dilatation of the esophagus and recurrent microaspiration 4 .…”
Section: Figurementioning
confidence: 99%
“…1 In addition to Heller myotomy and esophagectomy, 2 POEM has been established as a principal endoscopic therapeutic procedure in recent years. 2,3 Esophageal achalasia induces lung abnormalities due to dilatation of the esophagus and recurrent microaspiration. 4 A previous report showed that 50% of patients with esophagus achalasia had evidence of lung lesions such as tracheo-bronchial compression by the dilated esophagus, ground-glass opacities, nodules, fibrosis, air trapping, consolidation, and bronchiectasis on CT. 4 Furthermore, esophageal achalasia causes aspiration pneumonia, which can be lead to lung abscess.…”
mentioning
confidence: 99%
“…EndoFLIP may further help to measure secondary peristalsis in patients with esophageal symptoms, enabling the diagnosis of achalasia or other major esophageal motility disorders. Advances in fluoroscopy methodology, such as the timed barium swallow protocol and timed barium surface area measurement, have further added to the diagnostic arsenal when assessing a patient with esophageal symptoms [ 13 , 14 ].…”
mentioning
confidence: 99%
“…Achalasia is a dysphagia-causing neurodegenerative condition characterized by impaired esophageal motor function and a lack of lower esophageal sphincter (LES) relaxation. Achalasia is a relatively uncommon condition, with an annual incidence of 0.03-1.63/100,000 people and a prevalence of 10/100,000 [1]. Achalasia's specific pathophysiology is unknown at this time.…”
mentioning
confidence: 99%